A possibilidade da felicidade em Schopenhauer - Pamplona, Simião Severino (2017)
The aim of this work is to analyze the notion and possibility of happiness proposed by German philosopher Arthur Schopenhauer. This research is based on a study of his writings, especially The World as Will and Representation, volume 1, and Aphorisms on the Wisdom of Life. It also considers some critics from the Brazilian tradition of Schopenhauer studies. Proceeding from Schopenhauer’s thinking, this study offers an analysis of the understanding that life is suffering, investigates happiness through the satisfaction of desires, addresses the question of overcoming suffering through denial of the Will, and discusses happiness vis-à-vis the wisdom of life. The philosopher postulates that everyone suffers in whichever situation they find themselves: for, to live is to suffer. The source of endless suffering is the essence of the world itself; and it is this essence that Schopenhauer understands as the Will. According to him, the Will is a self-discordant, insatiable essence; and this conflicting characteristic expresses itself in each individual. Therefore, suffering is a manifestation of the Will. It is the halting of the Will, a blockage in which the Will prevents itself from achieving its ends in individuals. However, we can realize the overcoming of suffering by denial of the Will, an act by which some individuals no longer choose to affirm life through the renunciation of pleasure. We can also identify the possibility of achieving a happy and pleasant life, one that is understood as wise. Thus arises the question of understanding prospective notions of happiness, as well as the possibility of being happy in Schopenhauer’s philosophy, since even though he understands life as continuous affliction, he presents conditions that are indicative of happiness. Moreover, we can observe that happiness is understood in a negative way, that is, it is just the momentary absence of suffering. According to Schopenhauer, happiness does not appear as the acquisition of contentment or pleasure. We can still observe a state of overcoming suffering through denial of the Will, a state in which the individual becomes indifferent to all ailments. Further, we can realize that through knowledge of the wisdom of life, which is an acquisition of a character, people gain an understanding of how to behave in their lives, thereby allowing them to live as minimally unhappily as possible. This way of living produces the happiness presented in Schopenhauer’s eudemonology, according to which happiness is something that can be achieved in a processual way.